Kink of Subclavian Artery Mimicking Stenosis - Hatice S. Kemal; Aziz Gunsel; Murat Kocaoglu; Levent Cerit; Hamza Duygu (Case Reports in Cardiology)
The treatment for subclavian artery stenosis includes the more common endovascular therapy rather than surgical intervention in symptomatic patients. We present a case of a 79-year-old man with coronary artery bypass graft where subclavian artery stenosis was found incidentally. In this asymptomatic case, we have merged clinical and multiple imaging modalities to secure the diagnosis and treatment plan.